Shipboard operations - Lavery, H. I. (H. Irvine) (Routledge, 2011)
This book covers the knowledge of shipboard operations required by candidates for professional qualification as Chief Officer and Master Mariner. It deals with the basic routines and procedures, and the many regulations governing their use, for the safeand efficient operation of merchant ships. The book is also designated a fundamental text for the Maritime Transport paper of the Chartered Institute of Transport's membership examinations. The second edition takes into account recent developments intechnology and regulation, and in particular covers major interna